Perancangan Prototype Pendeteksi Warna Sampah Sensor Otomatis Berbasis Arduino terhadap Ketepatan Pemilahan Sampah - Nada Dhia Kamilia; Adib Suyanto; Iswanto Iswanto (Poltekkes Kemenkes Yogyakarta, 2021)
Plastic and paper are waste that are most produced by humans activities. Waste management is important to be implemented to minimize waste generation. The Arduino-based waste color de-tection prototype with TCS3200 sensor can make waste sorting easier. The purpose of this study was to determine the performance of Arduino-based automatic sensor waste color detection prototype in sorting accurately the plastic and paper waste which is represented by paper block objects with various colors. The research was a quasi-experiment with post-test only design. From the object sorting trial in duration of one hour that could conduct 100 repetitions, it was known that the red colored paper block has the highest succesfull sorting, and the blue one is the lowest. The study results show the average accuracy value of all types of colors, namely red, blue, green, and yellow is 95 %. The test of battery endurance showed that the prototype was last up to 14 hours 9 minutes and ended at 9,91Volt. To conclude, the prototype of waste color detection is successful and can sort objects in red, blue, green, and yellow color precisely.